Implementation of Qanun Baitul Mal on Zakat On Agriculture and Plantations in the Southwest of Aceh - Jamal, Anton; Fisa, Triansyah; Husamuddin, Husamuddin; Tasrizal, Tasrizal (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2025)
This research aims to explain the implementation of Qanun Baitul Mal No. 11 of 2018 in the Barat-Selatan Aceh (Barsela) region. The focus of the study is the application of Qanun Baitul Mal No. 11 of 2018 concerning the obligation to pay zakat from all agricultural and plantation yields, along with the influencing factors. The research was conducted in three regencies: Aceh Barat, Nagan Raya, and Abdya, using a qualitative descriptive method. Data collection techniques included in-depth interviews, observation, and literature review, which were then analyzed using legislative theory and the maqasid al-shari’ah approach. This study found that Barsela is a region with significant potential in agriculture and plantations, especially oil palm. However, public awareness to pay zakat from all agricultural and plantation yields in accordance with the provisions of the qanun remains very low. In general, the implementation of zakat is left to the understanding of the madhhab, without considering the logical reasoning (‘illat) and the objectives (maqasid al-shari’ah) behind the zakat obligation. As a result, zakat paid from agricultural and plantation yields is limited to staple food, in accordance with the provisions of the Shafi‘i madhhab. The contributing factors include a strong cultural attachment to the Shafi‘i madhhab, insufficient structural and functional support from related institutions, and a low level of understanding among stakeholders regarding the status and function of the qanun in the implementation of Islamic law (shari‘ah) in Aceh and its position within the legislative hierarchy.